Evaluation in situ digestibility of alfalfa in different grinds and textiles - Frank Akiyoshi Kuwahara; Gilberto Batista de Souza; Reinaldo de Paula Ferreira; Ciniro Costa; Paulo Roberto de Lima Meirelles (Acta Scientiarum. Animal Sciences, 2016)
Indigestible fractions of dry matter (iDM) and neutral detergent fiber (iNDF) in the feed of ruminants are mainly estimated by in situ incubation time with regard to particle size and textile types. Samples of alfafa, ground into three particle sizes, were analyzed. Samples, processed in a Willey mill with 1.0; 2.0 and 3.0 mm sieve pores, were conditioned in F57 (Ankon®), nonwoven (100 g m-2) and polyester textile bags measuring 4 x 5 cm. Material was divided into 13 incubation periods and 8 replications, and incubated in the rumen of two multiparous cows adapted to a 70:30 diet, roughage:concentrate, respectively, for 288h. iDM and iNDF rates were evaluated sequentially for non-digested percentage and data underwent analysis of variance (ANOVA p < 0.05); means were compared by tukey’s test (p < 0.05). Particle size and material employed for incubation affected iDM and iFDN at the initial periods of incubation (p < 0.05).